The comfort women: sexual violence and postcolonial memory in Korea and Japan - Soh, Chunghee Sarah (Worlds of desire, 2008)
Introduction: Gender, Class, Sexuality, and Labor under Japanese Colonialism and Imperialist War -- Part I. Gender and Structural Violence --1. From Multiple Symbolic Representations to the Paradigmatic Story -- 2. Korean Survivors¿ Testimonial Narratives -- 3. Japan¿s Military Comfort System as History - Part II. Public Sex and Women¿s Labor -- 4. Postwar/Postcolonial Memories of the Comfort Women -- 5. Private Memories of Public Sex -- 6. Public Sex and the State